2018
DOI: 10.1038/s41561-018-0111-y
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation of the Mesoproterozoic ocean and the evolution of complex eukaryotes

Abstract: 21The Mesoproterozoic Era (1,600-1,000 million years ago; Ma) has long been considered a 22 period of relative environmental stasis, with persistently low levels of atmospheric oxygen. 23 There remains much uncertainty, however, over the evolution of ocean chemistry during this 24 time period, which may have been of profound significance for the early evolution of 25 eukaryotic life. Here, we present rare earth element, iron speciation and inorganic carbon 26 isotope data to investigate the redox evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
92
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(98 citation statements)
references
References 42 publications
5
92
1
Order By: Relevance
“…Sulfur isotope studies from the same interval also suggested a small sulfate pool related to low oxygen levels in the atmosphere‐ocean system at that time (Guo et al, 2015; Luo et al, 2015). Recently, Zhang et al (2018) reported persistently negative Ce anomalies in REE patterns in the Gaoyuzhuang Member III in the Jixian section, which, along with a prominent negative carbonate δ 13 C excursion, was interpreted as evidence for a significant oxygenation event. This inference is further consolidated by the elevated I/(Ca + Mg) values from the same interval in the Gan'gou section, Yanqing area (Shang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sulfur isotope studies from the same interval also suggested a small sulfate pool related to low oxygen levels in the atmosphere‐ocean system at that time (Guo et al, 2015; Luo et al, 2015). Recently, Zhang et al (2018) reported persistently negative Ce anomalies in REE patterns in the Gaoyuzhuang Member III in the Jixian section, which, along with a prominent negative carbonate δ 13 C excursion, was interpreted as evidence for a significant oxygenation event. This inference is further consolidated by the elevated I/(Ca + Mg) values from the same interval in the Gan'gou section, Yanqing area (Shang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting evidence comes from the circa 1.60–1.54 Ga Gaoyuzhuang Formation (Lu et al, 2008; Li et al, 2010), North China. Recently, Zhang et al (2018) reported an integrated study of rare earth elements (REEs), Fe speciation, and inorganic carbon isotopes (δ 13 C carb ) from the Gaoyuzhuang Formation. The moderately negative Ce anomalies in the Member III of the Gaoyuzhuang Formation were interpreted as an imprint of significant oxygenation at circa 1.56 Ga. A negative δ 13 C carb excursion in the lower part of Member III was attributed to the oxidation of 13 C‐depleted organic carbon in response to the oxygen rise (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ca. 1560 Ma Gaoyuzhuang Formation from the Yanliao rift of the North China Craton has revealed fossil evidence for early eukaryote multicellularity (Zhu et al., ) and additional biogeochemical evidence for expanded ocean‐water oxygenation contemporaneous with the eukaryotic fossils (Zhang et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…If so, that was the first time (or possibly the first time since the Lomagundi excursion) that N-rich organic ocean floor sediment came into widespread contact with oxygenated water. This contact released organic N, leading to atmospheric O 2 increase, after which O 2 levels dropped once again 29,30 to the value imposed by the nitrogenase limit. Nitrogenase inhibition returns O 2 to low levels following O 2 increases, thus explaining an otherwise puzzling aspect of Proterozoic O 2 variation.…”
mentioning
confidence: 99%